Trust Based Security Model for IoT and Fog based Applications. - Abhijit J, Patil; G. Syam Prasad, Dr (International Journal of Engineering and Technology, 2018)
Wireless sensor networks (WSN’s) are becoming increasingly popular in the current Era. WSN and Smart Devices are key enablers for the Internet of things (IoT) and Fog Computing based applications and it brings IoT applications with enhanced capabilities for sensing and actuation. IOT is a very growing area and having wide scope for research. Integration of WSNs into IoT is today’s need. Adoptions to cloud computing, increasing use of automation of tools, Integration of internet into most activities of human had reached to the stage where Internet of Things based applications are becoming more popular today. Many new applications are now being developed in the field of IoT. The broad areas of application are Home automation, Smart cities, Retail, Agriculture, Manufacturing, Healthcare, Habitat Monitoring, Security and Surveillance etc. With this wide scope the applications are prone to many security threats. Providing Security for IoT and Fog computing-based applications is a Research Challenge. This paper tries to discuss with the common security attacks, Reasons, their counter measures and research directions. We are also proposing a Trust based Security model for implementing application layer level security in IoT and fog.